Functioning and quality of life in transition-aged youth on the autism spectrum – associations with autism symptom severity and mental health problems. (June 2023) - Backman, Anna; Zander, Eric; Roll-Pettersson, Lise; Vigerland, Sarah; Hirvikoski, Tatja
Abstract: Previous research notes difficulties in functioning and low quality of life (QoL) among transition-age youth on the autism spectrum, and poor mental health may contribute to these difficulties. This study examined the role of autism symptom severity and mental health problems on self-reported functioning and QoL in treatment-seeking transition-age autistic youth. The study included 140 autistic youth (16–25 years, M = 20.44 (SD = 2.95); n = 91 females [65%], n = 42 males [30%], n = 7 non-binary [5%]). We assessed functioning using a structured interview and QoL through a self-report questionnaire. Factors potentially associated with functioning and QoL were assessed using standardized self-report questionnaires of autism symptom severity, symptoms of anxiety and depression, and information from medical records. Participants reported functioning on the 90th percentile compared to general population norms, indicating significant disability, and also rated low overall QoL. Regression analysis showed that autism symptom severity and anxiety symptoms, and to some extent gender and having an ADHD diagnosis, explained 46% of the variance in overall functioning. Symptoms of anxiety and depression, and to a lesser extent, active friendship, explained 43% of the variance in QoL. Sampling limitations of the study include the overrepresentation of women and newly diagnosed participants. We highlight that functioning and QoL are multifactorial, necessitating a comprehensive assessment of transition-aged autistic youth, including mental health problems, to plan tangible interventions. Highlights: Treatment seeking transition-aged autistic youth without intellectual disability reported functioning difficulties and low quality of life. Autism symptom severity and mental health problems (symptoms of anxiety or depression; co-occurring ADHD) contributed to low functioning. The impact of anxiety and depression symptoms on QoL was found to be stronger than the influence of autism symptom severity. A comprehensive assessment, including self-reported autistic traits and mental health problems, would improve treatment planning.